1990
DOI: 10.1136/jcp.43.11.918
|View full text |Cite
|
Sign up to set email alerts
|

Detection of human papillomavirus type 16 DNA in carcinomas of the palatine tonsil.

Abstract: Twenty eight tonsillar carcinomas of various histological types were investigated for the presence of Epstein-Barr virus (EBV), cytomegalovirus (CMV), and human papillomavirus (HPV) types 6, 11, and 16 by in situ hybridisation using highly stringent procedures. In six cases an autoradiographic signal was obtained in the tumour cell nuclei with the HPV type 16 specific probe. As all of these cases were negative with EBVspecific probes (G Niedobitek, unpublished observations) we extended our study to other DNA t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
52
1
1

Year Published

1997
1997
2010
2010

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(57 citation statements)
references
References 18 publications
3
52
1
1
Order By: Relevance
“…Although the discovery of HPV in patients with OPSCC was reported first as early as 1990, 21 and its prognostic significance is well documented, [8][9][10][11] we observed that only 40.4% of radiation oncology practices (76 of 188 respondents) in our survey across the United States use screening for this prognostic marker. Academic practices screen twice as often as private practices.…”
Section: Discussionmentioning
confidence: 67%
“…Although the discovery of HPV in patients with OPSCC was reported first as early as 1990, 21 and its prognostic significance is well documented, [8][9][10][11] we observed that only 40.4% of radiation oncology practices (76 of 188 respondents) in our survey across the United States use screening for this prognostic marker. Academic practices screen twice as often as private practices.…”
Section: Discussionmentioning
confidence: 67%
“…HPV16, the type associated with the majority of cervical carcinomas, is the HR-HPV linked with the overwhelming majority of HPVpositive HNSCC (95%) (8)(9)(10). Other HR-HPV genotypes have been detected, including HPV18, HPV31, and HPV33.…”
mentioning
confidence: 99%
“…[2][3][4] As already suggested in 1983, these OPSCC are characterized by human papilloma virus (HPV) infection. 5 Viral DNA of high risk HPV 16 can be detected in nuclei of tonsillar cancer cells, 6 and is responsible for the vast majority of HPV positive tumors. 7 These tumors arise mainly in the lingual and palatal tonsils and are characterized as being a type of HNSCC with different distinct epidemiological, molecular, and clinical characteristics.…”
mentioning
confidence: 99%